A modeling of copt-h∞ controller and its performance investigation in opto electric system - Ramya, K; Kumar, KA Ramesh (International Journal of Advances in Applied Sciences, 2021)
This research work proposes Concentrated Opto Power Tracker (COPT) - H∞ controller modeling in Opto-Electric Converter System (OECS). The premeditated controller is designed using Riccati equation by considering the system uncertainties. State variable analysis approach is used for the analysis of the controller with system uncertainties. The designed controller is interfaced between the voltage Bias converter and the utility grid. With the proposed controller the grid voltages are estimated (eα,est, eβ,est) and is compared with the actual one (eα, eβ) to check for estimation errors and is observed that the estimation errors are close to zero. The Proposed work concentrates mainly on the modeling of Opto-Electric Converter System (OECS) for parameter uncertainties in the system for system stability. Modeling, Simulation and experimental results are done in MATLAB/SIMULINK to verify the performance of the Concentrated Opto Power Tracker (COPT) - H∞ controller.